PERBANDINGAN SUSUNAN DAN KANDUNGAN ASAM LEMAK KELAPA MUDA DAN KELAPA TUA (Cocos nucifera L.) DENGAN METODE GAS KROMATOGRAFI - Rita Hayati (Jurnal Floratek, 2009)
Comparation of Composition and Content of Fatty Acid in Young Coconut and Mature Coconut (Cocos Nucifera L.) with Chromatografi Method Rita Hayati Fakultas Pertanian Unsyiah, Darussalam Banda Aceh ABSTRACT Objectives of this research was to evaluate the differences in composition and contents of fatty acid between the young and mature coconut and to provide information for health aspects.  Results showed that  content of  lauric acid and myristic acid of young coconut were lower than those of mature coconut.  Medium Chain Glycerides (MCT) C8 of young coconut was also lower than that of mature coconut.  Coconut oil rate of mature and young coconut at this study was 131,80 %.